PENERAPAN SISTEM DAN PROSEDUR AKUNTANSI PENGELOLAAN DANA DESA DI DESA TINCEP KECAMATAN SONDER KABUPATEN MINAHASA - Tangkaroro, Kenny Larony; Ilat, Ventje; Wokas, Heince (Universitas Sam Ratulangi, 2017)
The purpose of this study is to analyze the problems experienced by villages related to the management of village funds and also to analyze the Application of Accounting System for Village Fund Management which includes Cash Receipts, Cash Expenditures, Fixed Assets, and Taxes. This research was conducted in Tincep Village, Sonder Sub District, Minahasa District. This research uses descriptive qualitative method. The results show that the management of village funds in Tincep Village is in accordance with Permendagri No.113 of 2014 and the priority of the use of village funds in Tincep Village is also appropriate based on PermenDesaPDTT No. 22 of 2016, The application of accounting system in Tincep village is in accordance with the legislation, but if viewed from the side of administrative supervision is still not fully in accordance with the provisions, especially in the process of cash expenditures that have not been accountable and often not appropriate procedures. Therefore the author suggests that the need for a computerized accounting system so that later every accounting process can be done quickly and the output of financial statements will also be more reliable than the reporting manually, also in the future it is expected that management related to village fund can be done more accountable and transparent.Keywords :Â Management of village finances, accounting information system, village fund